2019
DOI: 10.1016/j.cell.2018.11.046
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumor Cell Clustering Shapes DNA Methylation to Enable Metastasis Seeding

Abstract: SummaryThe ability of circulating tumor cells (CTCs) to form clusters has been linked to increased metastatic potential. Yet biological features and vulnerabilities of CTC clusters remain largely unknown. Here, we profile the DNA methylation landscape of single CTCs and CTC clusters from breast cancer patients and mouse models on a genome-wide scale. We find that binding sites for stemness- and proliferation-associated transcription factors are specifically hypomethylated in CTC clusters, including binding sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

32
625
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 664 publications
(659 citation statements)
references
References 69 publications
32
625
1
1
Order By: Relevance
“…The question of whether different cancers use a unique set of stemness molecules to induce cluster formation (such as CD24 in the current study) is worth further investigation. A recent study reported that CTC clusters showed a profile of overmethylation that promoted cancer stemness of the patient breast cancer cells, supporting our hypothesis. Therefore, our study provides a good in vitro model to study the relationship between cancer stemness and cluster formation and metastasis in colon cancer.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The question of whether different cancers use a unique set of stemness molecules to induce cluster formation (such as CD24 in the current study) is worth further investigation. A recent study reported that CTC clusters showed a profile of overmethylation that promoted cancer stemness of the patient breast cancer cells, supporting our hypothesis. Therefore, our study provides a good in vitro model to study the relationship between cancer stemness and cluster formation and metastasis in colon cancer.…”
Section: Discussionsupporting
confidence: 88%
“…24 Indeed, some recent studies have demonstrated that breast cancer CTC clusters possess much high metastatic potential and were more tumorigenic and resistant to apoptosis. 4,25 Therefore, the clustering process can be regarded as an initial mechanism for cancer cells to maintain their tumorigenicity during development, which is particularly relevant to CTCs during circulation and initiating new tumours at secondary sites. Understanding this mechanism is therefore essential for developing effective intervention therapies of metastasis in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic value of CTCs has been proven in abundant studies, especially in patients with advanced BC. 2,28,29 However, there is still a lack of consistent conclusions regarding whether CTCs could be applied as an independent predictor of NCT effectiveness in early BC. In this study, we used the CanPatrol technique to determine the relationship circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Other data suggested that intravascular aggregation and proliferation could be excluded as potential sources of tumour clusters due to the unfavourable conditions present in the bloodstream [9]. Very recently, Gkountela et al [10] demonstrated that -in strong contrast to circulating tumour cells -the pattern of transcription factors in tumour clusters reveals similarities to embryonic stem cells along with increased proliferation. However, some cluster processes are still unknown regarding their genesis,transit and settlement and about the precise cellular and molecular mechanism.…”
Section: Introductionmentioning
confidence: 99%